Efficacy of stem cell secretome loaded in hyaluronate sponge for topical treatment of psoriasis. Issue 2 (21st February 2023) - Carrillo, Daniela; Edwards, Natalie; Arancibia‐Altamirano, David; Otárola, Fabiola; Villarroel, Cynthia; Prieto, Catalina P; Villamizar‐Sarmiento, María Gabriela; Sauma, Daniela; Valenzuela, Fernando; Lattus, José; Oyarzun‐Ampuero, Felipe; Palma, Verónica
Abstract: Psoriasis vulgaris is an inflammatory disease characterized by distinctive skin lesions and dysregulated angiogenesis. Recent research uses stem cell secretion products (CM); a set of bioactive factors with therapeutic properties that regulate several cellular processes, including tissue repair and angiogenesis. The aim of this work was to evaluate the effect of CM of Wharton's gelatin MSC (hWJCM) in a treatment based on the bioactivation of a hyaluronic acid matrix (HA hWJCM) in a psoriasiform‐like dermatitis (PD) mouse model. A preclinical study was conducted on PD mice. The effect of hWJCM, Clobetasol (Clob) gold standard, HA Ctrl, and HA hWJCM was tested topically evaluating severity of PD, mice weight as well as skin, liver, and spleen appearance. Treatment with either hWJCM, HA Ctrl or HA hWJCM, resulted in significant improvement of the PD phenotype. Moreover, treatment with HA hWJCM reduced the Psoriasis Area Severity Index (PASI), aberrant angiogenesis, and discomfort associated with the disease, leading to total recovery of body weight. We suggest that the topical application of HA hWJCM can be an effective noninvasive therapeutic solution for psoriasis, in addition to other skin diseases, laying the groundwork for future studies in human patients.